Developments in Language Theory 16th International Conference, DLT 2012, Taipei, Taiwan, August 14-17, 2012. Proceedings - Yen, Hsu-Chun.; Ibarra, Oscar H.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 16th International Conference on Developments in Language Theory, DLT 2012, held in Taipei, Taiwan, in August 2012. The 34 regular papers presented were carefully reviewed and selected from numerous submissions. The volume also contains the papers or extended abstracts of 4 invited lectures, as well as a special memorial presentation in honor of Sheng Yu. The topics covered include grammars, acceptors and transducers for words, trees and graphs; algebraic theories of automata; algorithmic, combinatorial and algebraic properties of words and languages; variable length codes; symbolic dynamics; cellular automata; polyominoes and multidimensional patterns; decidability questions; image manipulation and compression; efficient text algorithms; relationships to cryptography, concurrency, complexity theory and logic; bio-inspired computing; quantum computing.
Keywords: Computer science; Coding theory; Logic design; Computational complexity; Computer Science; Computation by Abstract Devices; Mathematical Logic and Formal Languages; Logics and Meanings of Programs; Coding and Information Theory; Discrete Mathematics in Computer Science